A REVIEW ON PROPERTIES, APPLICATIONS AND TOXICITIES OF METAL NANOPARTICLES - G., SANGEETHA; N., USHA; R., NANDHINI; P., KAVIYA; G., VIDHYA; B., CHAITHANYA (International Journal of Applied Pharmaceutics, 2020)
Nanotechnology is a broad and novel technology related to all branches of science. However, in the Pharmaceutical industry, it plays an immense role in the drug delivery system. Nanotechnology applied on metal-based drug delivery systems varies; the size ranges from 100 nm or less. Metallic nanoparticles are existing the world from the 4th century. The noble metals, like gold and silver have attracted many researchers in the class of anticancer and anti-microbial. Metallic nanoparticles are not only used in the biomedical applications also have major functions in the domain of textiles, agriculture, photography, etc. Various metals are found in various applications in the biomedical industries. At the same time, the metallic nanoparticles have been evidences of remarkable toxicity in various studies. The rationale behind this topic was that the properties, applications and toxicity of individual metal nanoparticles. As this study have not been compiled and reported. So, in the current review, the gap was filled. The main sources for the preparation of the manuscript are Pubmed, Elsevier and google scholars. Keywords used includes metallic nanoparticles, reported toxicity of metals in drug delivery, applications of metals in drug delivery, history of novel metals in drug delivery, etc. Approximately 400 reviews and academic papers were reviewed to compose the manuscript and sorted by reference to the need for a manuscript.